Knowledge and practice of hand hygiene among practicing physical therapists of Lahore after covid-19 pandemic - Ubaid, Qadeer; Zafar, Amirah; Wajahat Subhani, Muhammad; Asif, Farhan; Fatima, Mahnoor; Raza, Asim (International Journal of Pathology, 2024)
Background: Hand hygiene has become an important factor after Covid-19 pandemic. The practicing physical therapists are more prone to infections due to direct contact with patients. The knowledge and practice is therefore very important for them. Methods: This study is descriptive cross sectional. It was conducted among practising physiotherapist of CMH Hospital and private clinical setups of Lahore. Non probability convenient sampling was used for participant selection. Window SPSS 23.0 was used for statistical analysis. Results: The data was collected from 206 participants. 123 participants were males and 83 participants were females. In answer to if the participants received education of hand hygiene, 81 participants answered no and 125 answered in yes. In an another question about the use of alcohol based hand rub for hand hygiene 60 participants answered no and 146 participants answered yes. The total score for knowledge and practice of hand hygiene was 64 from question number 3-11. Question number 7 of the questionnaire consists of further 8 parts, that’s why the total score becomes 64. The mean score percentage was 70.59±16.94. In question 12 the participants were asked about who have given the idea to perform hand hygiene, 104 told that their manager, 89 told that their peer and 13 participants told that their patients remind them about hand hygiene. The participants faced some barriers in this regard e.g. out of product material, too busy in work, forget about hand hygiene etc. Conclusion: The study shows that most physical therapists of Lahore have better knowledge and practice of hand hygiene. Both male and female practicing physical therapists are well aware of the importance of hand hygiene. But few barriers such as non-convenient, out of product material influence in practicing hand hygiene.